Publicidade e propaganda no cinema: um estudo sobre os anos 1980 - Kaczorowski, Leandro José Borsarin (My University, 2025)
This paper explores the history of cinema and the impact of advertising and product placement in 1980s films, with an emphasis on three significant works: Ferris Bueller's Day Off (1986), They Live (1988), and Top Gun (1986). The research examines how these films strategically integrated brands and shaped viewers' consumption habits. The study combined quantitative methods, using surveys applied to a random sample, and qualitative methods, through focus groups that deepened the analysis of audience perceptions. An interview with a cinema professional further enriched the discussion about marketing strategies and their cultural impacts. The results highlighted cinema as a tool for advertising and propaganda, and a more critical and attentive audience regarding messages in films, considering those from the 1980s more subtle than current ones. Moreover, the study underscored the sociocultural and historical influence of cinema and the balance between narrative and messaging achieved during that decade. [resumo fornecido pelo autor]
Este trabalho explora a história do cinema e o impacto da publicidade e do product placement nos filmes dos anos 1980, com ênfase em três filmes significativos: Curtindo a Vida Adoidado (1986), Eles Vivem (1988) e Top Gun: Ases Indomáveis (1986). O estudo analisa como essas obras cinematográficas integraram marcas de forma estratégica e moldaram os hábitos de consumo dos espectadores. A pesquisa combinou métodos quantitativos, com formulários aplicados a uma amostra aleatória, e qualitativos, por meio de grupos focais que aprofundaram a análise das percepções do público. A realização de uma entrevista com um profissional da área do cinema enriqueceu a discussão sobre estratégias de marketing e seus impactos culturais. Os resultados destacaram o cinema como ferramenta publicitária e propagandística e um público mais crítico e atento às mensagens nos filmes, considerando as dos anos 1980 mais sutis que as atuais. Além disso, foi pontuada a influência sociocultural e histórica do cinema e o equilíbrio entre narrativa e mensagem encontrado na década. [resumo fornecido pelo autor]
Keywords: Publicidade; Propaganda; Cinema